DETERMINAN OPINI ATAS LAPORAN KEUANGAN PEMERINTAH DAERAH DI INDONESIA - Dwi Kusumawati Kusumawati; Dwi Ratmono (Diponegoro Journal of Accounting, 2017)
This research aims to analyze the determinant factors that affect the opinion of the financial statement of the local government. The dependent variable in this research is audit opinion from the Audit Board of Republic of Indonesia on the financial statement of the local government. The independent variables were tested in this research is weakness of the internal control, non-compliance with laws and regulations, the age of local government, size of local government, the dependance level, human resource quality, follow-up of audit recommendation, the type of local government and the forms of local government. This research uses secondary data devided from the results of the examination report the Audit Board on the local goverment financial report period in 2015. The total sample as many as 497 local government in Indonesia. The analytical method used is ordinal logistic regression or ordered logistic regression. The results showed that the weakness of internal control and the dependance level have significant negative effect on opinion of the financial statement of the local government. The follow-up of audit recommendation have significant positive effect on opinion of the financial statement of the local government. Non-compliance with laws and regulations, the age of local government, size of local government, human resource quality, the type of local government and the forms of local government does not have a significant effect on opinion of the financial statement of the local government.